Exploring Nursing Students Perceptions of Google Tools in English for Nursing Learning - Fini Widya Fransiska; Bastian Sugandi (EXPOSE (Journal of English Education and for Specific Purpose), 2024)
English Nursing Language plays an important role in supporting nursing students' communication skills, especially in facing the needs of healthcare services globally. Unfortunately, students often find learning English Nursing Language difficult due to limited medical vocabulary, low confidence in speaking, and the dominance of clinical practice. Digital technology offers opportunities to use online platforms such as Google tools for more flexible and contextual learning. This study examines students' perceptions of using Google tools in learning English Nursing Language as a general course. The mixed-methods approach was used, with quantitative data from 60 students via Likert questionnaires and qualitative data from interviews with five students. Learning utilized Google Classroom, Google Meet, Google Docs, and Google Forms. Data were analyzed using descriptive statistics and thematic analysis. The results show that students are positive about Google tools, rating ease of use, flexible access, engagement, and high relevance. Interviews indicated that Google Meet increased speaking confidence, and Google Docs supported collaborative writing. The main obstacles were internet connectivity and limited medical vocabulary. The study concludes that pedagogically and contextually integrated Google tools can support effective learning of English Nursing Language.